PENGARUH LATIHAN TENDANGAN MAWASHI GERI DENGAN BEBAN TERHADAP KECEPATAN TENDANGAN PADA ATLET KUMITE KARATE JUNIOR PUTRA RUMBAI CHEVRON - Novriyan, Grace; Slamet, Slamet; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this study is still lack of speed at the time of kicks on kumite athletes karate junior son tassel chevron. Based on these problems the authors give the form of mawashi geri exercise with load. This study was conducted to find out how much influence mawashi geri practice with the burden of kicking speed on kumite athlete karate junior son frame chevron, so that at the time of attack kicks get maximum kick results. This type of research is experimental with one group pretest-posttest design research. The population in this study is the kumite karate junior son of framework chevron 4 men. The sampling technique used is total sampling, where the entire population of 4 people is sampled. With a kick-speed skill test instrument, a descriptive analysis and normality test using liliefors test at a significant level of α (0.05) resulted in a pretest average kick rate of 16.25. Furthermore, given mawashi geri training with load for 16 times meeting at kumite junior karate athlete 4 fraction chevron man. Then performed posttest speed kick mawashi geri yielded an average of 19.75. Based on the results of pretest and posttest data analysis there is a difference in numbers which increased by 3.5. From t test analysis yield Thitung equal to 5,468 and Ttable equal to 2,353 mean tcount> ttable. It can be concluded that mawashi geri practice with load influences on the result of increased kick speed at kumite athlete karate junior son of tassel chevron.Keywords: Mawashi Geri, kick speed